Prinsip Bangunan Sehat Pada Gedung Perkuliahan Teknik Sipil Politeknik Negeri Pontianak - Susanto, Agus; Z., Andi Zulestari; Ikayanti, Palupi (Politeknik Negeri Pontianak, 2023)
The Covid 19 pandemic resulted in millions of deaths including in Indonesia in general and Pontianak in particular. Patients exposed to positive exposure to Covid in West Kalimantan Province alone, the number of people exposed to positive Covid 19 as of 2 May 2020 were 61 patients and 34 of them were in Pontianak so that the government emphasized every agency to carry out social distancing and end up with PSBB or Large-Scale Social Restrictions. In terms of education, this social distancing instruction and PSBB resulted in the termination of face-to-face lectures and replaced with online activities including lectures at the Pontianak State Polytechnic. In addition to the implementation of the applied health protocols, educational buildings in general and lecture buildings in particular must have health standards. Therefore, it is necessary to study the existing building and space patterns and their relation to the activities of the actors in the lecture building which refer to the principles of healthy buildings. The final result of this research is expected to be able to bring up a pattern of lecture buildings that meet health building standards and be able to adapt and anticipate environmental changes that will occur in the future. This type of research is a descriptive study using qualitative and quantitative approaches. In this study, the quantitative method used is in the form of numbers obtained from the measurement results, while the qualitative method is in the form of analysis based on three (3) dimensional location images which refer to the principles of a healthy building. The result is identifying how the arrangement of lecture buildings in the Pontianak State Polytechnic environment is not yet in accordance with the principles of healthy building